Comparing official and literary discourses оn sino-soviet border crossings of 1962 (Journal of history, 2019)
Оfficial discourse (soviet and Chinese) interpreted the reasons of ethnic groups exodusetatist – border defense, L control over population migrations, economic losses and maintenance ofbilateral relations at certain level. Q.Zhumadilov drew the line of affirmation of Kazakhs migration fromChina as salvation, but essential ethno-demographic resource for maintenance of ethnic potential ofKazakhs in soviet Kazakhstan. The official soviet discourse being diplomatic in form, especially, when itconcerned the regulating technicalities with the Chinese officials, was civic in nature. The Soviet Unioninterpreted the right to patronize the former Russian/ soviet citizens residing in China through the missionor responsibility to protect. Although the main motivation was to gain as many loyal to the sovietregime human force for realization of state building projects within the USSR. The Chinese discoursewas mainly political administrative in form, and legal in nature, as it referred to the right to supervise thepopulation of the province and prevent intervention of alien forces into it domestic sphere